KEPUASAN PASIEN RAWAT INAP MASA PANDEMI COVID-19 DI RUMAH SAKIT XYZ BATANG - Rosa Maharani; Sentot Suciarto (LPPM Universitas Pekalongan, 2022)
Since the onset of the Covid-19 pandemic, all health workers have not had experience dealing with Covid-19. Health workers must adapt to changing conditions, starting from the implementation of Covid-19 management guidelines, new guidelines that must be implemented, changes in nurse-patient interactions, the use of Personal Protective Equipment, anxiety about contracting Covid-19 or transmitting it to families. With the implementation of this application, there will be ups and downs in patient visits for treatment at the hospital. Hospitals are required to strive to provide satisfaction to every patient, especially for users of health services for the community. Health service is a concept used in providing health services to the community in order to create satisfaction. Patient satisfaction is a very meaningful element for a service user, because it is able to create and retain customers well. This research is located at XYZ Batang Hospital, Central Java. The population in this study were inpatients in class 1A at XYZ Hospital with a time period of 1 month starting from June 1, 2021 to July 1, 2021. The population was taken from the data on the number of patients who entered the period June 1, 2021 - July 1, 2021 as many as 150 patients at XYZ Batang Hospital.